TEKNIK DAN PENDEKATAN PENANAMAN NILAI DALAM PROSES PEMBELAJARAN DI SEKOLAH - Muhtadi, Ali (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Values are what people believe to be right and are standardv to judge something to be good, right, valuable and precious. Values drive people 's live, give meanings to live and legalize people's behaviors. Therefore, individual's values can have effects on society and national characteristics. Education seems to fail to educate universal values such as honesty, patience, modesty and trustworthy. This is because educational process that occurred lately is so merely mechanistic learning that negelected the essence of education as wizys to internalize universal values in life. There are some learning techniques for teachers to use in educating value to their students, such as indoctrination technique, moral reasoning technique, consequence forecasting technique, clnrification technique and internalization technique. The approaches that teacher can use to educate value through learning process al school are experience approach, making it accustomed, emotional, rational, functional and role model approach.